Guillain–Barre syndrome and link with COVID-19 infection and vaccination: a review of literature - Valaparla, Vijaya Lakshmi; Rane, Schweta P.; Patel, Chilvana; Li, Xiangping (Frontiers in Neurology, 2024)
Background Guillain–Barré syndrome (GBS) is an autoimmune disease associated with significant morbidity. A wide variety of infectious and non-infectious triggers have been identified to be associated with GBS. COVID-19 has gained attention in recent years for its role in GBS pathogenesis. Our study aims to review the literature on GBS and its epidemiological and pathophysiological association with COVID-19. Description Recent literature on GBS associated with COVID-19 infections, such as case reports, case series, systematic reviews, and large-scale epidemiological studies, were reviewed. We also reviewed studies that included vaccines against COVID-19 in association with GBS. Studies that focused on understanding the pathobiology of GBS and its association with infectious agents including COVID-19 were reviewed. Conclusion Despite a lack of consensus, GBS is strongly associated with COVID-19 infection. The exact pathophysiological mechanism regarding COVID-19 as a causative agent of GBS is unknown. Mechanisms, such as the proinflammatory state, triggering of autoimmunity, and direct viral invasion, are postulated and remain to be investigated. Adenovirus vector vaccines are most likely associated with GBS, and the consensual reports clearly suggest mRNA vaccines are associated with low risk and may be protective against GBS by reducing the risk of COVID-19 infection.